'Som escola'. The construction of an inclusive intercultural community in a school undergoing transformation. Issue 1 (2nd January 2021) - Molina Diaz, Maria; Sales, Auxiliadora
ABSTRACT: The present article describes a study carried out in a rural school in the province of Valencia (Spain) that is currently immersed in a process of transformation towards becoming an inclusive intercultural school. The objective of this study is to learn about the process of constructing the school's educational community and the factors involved in this process. The study used intrinsic case study methodology in which, through interviews, focus groups, participatory social diagnostic techniques and participant observation, we examine how this educational community is being constructed. The results show the dynamism and complexity of this process. The search for identity symbols, the need to continually inspire motivation among the members of the community and the emergence of a dichotomous discourse determines its evolution. The democratic participation of the community is demonstrated as a core element in the process of constructing this inclusive intercultural educational community.